Influence of parameters of digital conversion signal fluctuations on the accuracy determination of dynamic displacements of structures - Філоненко, С.Ф.; Корнієнко, І.К.; Косицька, Т.М. (Proceedings of National Aviation University (archive), 2009)
The results of experimental researches of influencing a sampling interval of registered acceleration and speed oscillation signals on amplitudes the signals of speed and displacement, after fulfillment the conversions operations are reviewed. Are shown the main regularity a change of signals speed and displacement output amplitudes from time of conversion at given sampling intervals. Is determined, that the sampling interval does not influence to change a maximum amplitudes of converted signals provided that the conversion implements from time constants, that value is peer to which one to half part of period a speed and acceleration oscillations input signals.